Impact of Knowledge Dissemination on Employee-Based Brand Equity: Mediating Role of Brand Identification and Emotional Attachment - Liu, Han (Frontiers in Psychology, 2022)
The challenging competition situation in the market forces the organizations to recognize the crucial role of branding. The extent of studies focused on financial and customer perspectives and ignored the importance of employee-based brand building in the organization. Employee-based brand equity plays a vital role in increasing organizational performance. Hence, this study put effort into brand-building and recognized many factors that develop employee-based brand equity for organizations. This study examines the role of internal knowledge dissemination and employees-based brand equity through brand identification and emotional attachment. This study also assessed the direct relationship between internal knowledge dissemination and brand identification, internal knowledge dissemination and emotional attachment, brand identification and employee-based brand equity, and emotional attachment and employee-based brand equity. For this purpose, this study adopted a convenient sampling technique and questionnaire survey method and gathered data with 712 sample sizes from employees of various clothing brands in China. For empirical examination of the data, this study considered the partial least square structural equation modeling technique and analyzed data through Smart PLS 3.3.3 software. The outcomes revealed that internal knowledge dissemination negatively influences employee-based brand equity. This study found a positive direct association between internal knowledge dissemination and brand identification, internal knowledge dissemination and emotional attachment, brand identification and employee-based brand equity, and emotional attachment and employee-based brand equity. Moreover, this study found that emotional attachment and brand identification positively mediate the relationship between internal knowledge dissemination and employee-based brand equity. This study guides the managers that rational dissemination of the internal knowledge enhances employees' brand identification and emotional attachment; as a result, brand identification and emotional attachment enhance the employee-based brand equity. Finally, this study's limitations and future research opportunities are also discussed.